Socio-Economic Determinants of Food Insecurity in Punjab, Pakistan - Mushtaq, Samina; Yasin, Mian Ghulam (Annals of Human and Social Sciences, 2025)
This study is an attempt to examine these socioeconomic determinants that affect food security in Punjab, Pakistan. Food insecurity persists as a significant issue in Pakistan, shaped by complex socioeconomic factors affecting the nation's food accessibility, availability, and utilization. In order to achieve study objective, a cross sectional field survey was conducted, and a sample of 299 household heads was selected from Punjab, Pakistan using cluster/geographic sampling technique. The data was acquired through interview schedule. The collected data thus was analyzed via descriptive statistics and Pearson correlation. The study findings revealed that low income, low education, unemployment, inflation, and large family size are the key socioeconomic determinants of food insecurity in Punjab, Pakistan. The study suggested that impact of these socioeconomic determinants on food security can be alleviated through multi-sectoral strategies i.e., fair wages, better access to education, increased job opportuinities, controlled inflation, and family planning awareness, primarily targeting at-risk populations.